A rosary of hundred beads : a century of shruks by Nund-Rishi - Nund-Rishi (J & K Academy of Art, Culture and Languages, 1981)
Teachings of Shaiḵẖ al-ʻĀlam, also known as Nund-Rishi, Muslim saint from Kashmir.